Freedom fire - Older, Daniel José (Older, Daniel José. Dactyl Hill Squad, 2020)
The group from the Colored Orphan Asylum led by Magdalys Roca ride the back of a pteranodon to find Magdalys's brother, Montez, who fights in Louisiana for an all-black regiment in the Union Army. But one of the group is not what she seems and wants to use Magdalys's psychic ability to communicate with dinosaurs for her own nefarious purposes.